"BOOM, so it will be like an attack" Demonstrating in a dance class through verbal, sound and body imagery. (June 2021) - Douglah, Jessica
Abstract: The present study investigates how the teacher in a show dance class demonstrates choreography to a group of learners (dancers) using imagery as a teaching strategy. The overall aim is to explore the pedagogical task of demonstrating with the help of imagery and to understand how different multimodal resources create prerequisites for learning. The data consist of ethnographic fieldwork and video recordings from a show dance practice. The participants are a teacher and a group of non-professional learners aged between 16 and 24 years. The analysis is based on the framework of ethnomethodological conversation analysis (EMCA). The analysis shows that the use of imagery is common, and that verbal language is a resource that co-occurs with both sound and body in these demonstrations. These multimodal resources interplay in a complex way, and the different resources used by the teacher cooperate to create meaning for the dancers. None of the different types of imagery – verbal, sound or body –seem to fully function unless they are used together with at least one other resource. Further, the analysis shows that the use of imagery as a teaching strategy is emergent in interaction and not predetermined.